Glycerol as a cryoprotectant agent to the entomopathogenic nematodes Heterorhabditis spp. and Steinernema spp. - Guide, Bruna Aparecida; Alves, Viviane Sandra; Fernandes, Thiago Augusto Paes; Pinhatari Ferreira, Fábio; Neves, Pedro Manuel Oliveira Janeiro (Semina: Ciências Agrárias, 2016)
The difficulty of storage and conservation of entomopathogenic nematodes (ENPs) is one of the major obstacles for the expansion of its use in the control of biological pest and in the maintenance of collections of these organisms. The objective of this study was to evaluate cryopreservation as a storage and conservation method for ENPs, using glycerol as cryoprotectant. Infective juveniles (IJs) of the species Heterorhabditis amazonensis (RSC 05), H. bacteriophora (HP88), Steinernema feltiae (Sn) and S. carpocapse (IBCB-n02) were subjected to the following treatments: (A) immersion in glycerol at different concentrations (10, 13 and 15%); (B) different exposure times of the isolates to glycerol (24 and 48 hours); and (C) two freezing times in liquid nitrogen (LN) at -196 ºC (24 and 168 hours). Each treatment was replicated four times, and the design was completely randomized in a factorial 3x2x2 (glycerol concentrations x glycerol exposure time x freezing time in LN). IJs survival was evaluated after each exposure time to glycerol and freezing time in LN. Data were subjected to analysis of variance, and means were compared by the Tukey test. S. feltiae and S. carpocapse survived when exposed to glycerol at 10, 13 and 15% for 24 and 48 hours. After storage in LN for 24 and 168 hours, only S. feltiae survived when exposed to glycerol for 48 hours at concentrations of 10, 13 and 15%, with 40.5; 58.2; and 57.7% survival, respectively. S. feltiae was able to infect Galleria mellonella larvae after freezing. However, for the freezing time of 168 hours, 90% reduction in infectivity was observed.